The Chachil Limestone (Pliensbachianeearliest Toarcian) Neuquén Basin, Argentina: UePb age calibration and its significance on the Early Jurassic evolution of southwestern Gondwana - Leanza, Hector Armando (2013)
New radiometric UePb ages obtained on zircon crystals from Early Jurassic ash layers found within beds of the Chachil Limestone at its type locality in the Chachil depocentre (southern Neuquén Basin) confirm a Pliensbachian age (186.0 0.4 Ma). Additionally, two ash layers found in limestone beds in Chacay Melehue at the Cordillera del Viento depocentre (central Neuquén Basin) gave Early Pliensbachian (185.7 0.4 Ma) and earliest Toarcian (182.3 0.4 Ma) UePb zircon ages. Based on these new datings and regional geological observations, we propose that the limestones cropping out at Chacay Melehue are correlatable with the Chachil Limestone. Recent data by other authors from limestones at Serrucho creek in the upper Puesto Araya Formation (Valenciana depocentre, southern Mendoza) reveal ages of 182.16 0.6 Ma. Based on these new evidences, we consider the Chachil Limestone an important Early Jurassic stratigraphic marker, representing an almost instantaneous widespread flooding episode in western Gondwana. The unit marks the initiation in the Neuquén Basin of the Cuyo Group, followed by widespread black shale deposition. Accordingly, these limestones can be regarded as the natural seal of the Late Triassic eearliest Jurassic Precuyano Cycle, which represents the infill of halfgrabens and/or grabens related to a strong extensional regime. Paleontological evidence supports that during Pliensbachianeearliest Toarcian times these limestones were deposited in western Gondwana in marine warm water environments.